Analisis Faktor yang Berhubungan dengan Kepatuhan Berobat Mantan Pasien Kusta - Burhanuddin, Nurfardiansyah; Amelia, Andi Rizki; Nurgahayu, Nurgahayu (Window of Health : Jurnal Kesehatan, 2018)
Leprosy is a disease attached to negative views and discrimination, both within and from the community, family members or leprosy itself, such as avoiding direct contacts to be ostracized and discarded by the community from where they live. Stigma in society makes lepers alive in fear and embarrassment to be in the midst of society. Besides various names about leprosy that illustrate how dangerous and disgusting the disease is. Another thing, the existence of various beliefs about the origin of this disease causes the leprosy people feel guilty, resigned and embarrassedThe purpose of this study is to determine any factors related to the compliance of the treatment of former leprosy patients at Dr. Leper Hospital. Tadjuddin Chalid Makassar.Penelitian is this research is quantitative research, which is done to determine the effect of quality of health service to the compliance of treatment of former leprosy patients at Dr. Leper Hospital. Tadjuddin Chalid Makassar. The sampling technique of the sample is calculated using the formula quoted from Notoatmodjo (1993) with the number of samples ie 87 ex-patients in Leprosy Hospital Dr. Tadjuddin Chalidditentukan simple random sampling.Results expected in this study people who are detected as leprosy patients to routinely perform treatment in order to avoid leprosy defects resulting from leprosy.